A link between mitochondrial gene expression and life stage morphologies in Trypanosoma cruzi. Issue 5 (5th February 2020) - Ramirez‐Barrios, Roger; Susa, Emily K.; Smoniewski, Clara M.; Faacks, Sean P.; Liggett, Charles K.; Zimmer, Sara L.
Abstract: The protozoan Trypanosoma cruzi has a complicated dual‐host life cycle, and starvation can trigger transition from the replicating insect stage to the mammalian‐infectious nonreplicating insect stage (epimastigote to trypomastigote differentiation). Abundance of some mature RNAs derived from its mitochondrial genome increase during culture starvation of T. cruzi for unknown reasons. Here, we examine T. cruzi mitochondrial gene expression in the mammalian intracellular replicating life stage (amastigote), and uncover implications of starvation‐induced changes in gene expression. Mitochondrial RNA levels in general were found to be lowest in actively replicating amastigotes. We discovered that mitochondrial respiration decreases during starvation in insect stage cells, despite the previously observed increases in mitochondrial mRNAs encoding electron transport chain (ETC) components. Surprisingly, T. cruzi epimastigotes in replete medium grow at normal rates when we genetically compromised their ability to perform insertion/deletion editing and thereby generate mature forms of some mitochondrial mRNAs. However, these cells, when starved, were impeded in the epimastigote to trypomastigote transition. Further, they experience a short‐flagella phenotype that may also be linked to differentiation. We hypothesize a scenario where levels of mature RNA species or editing in the single T. cruzi mitochondrion are linked to differentiation by a yet‐unknown signaling mechanism. Abstract : The causative agent of Chagas disease, Trypanosoma cruzi, undergoes many morphological and physiological changes as it cycles between its insect vector and mammalian hosts. T. cruzi life stage alterations include changes to expression of its mitochondrial genome. In this study, we pursue possible functional consequences of these alterations of mitochondrial gene expression.